Crossroads of coagulation and innate immunity: the case of deep vein thrombosis. (30th June 2013) - Schulz, C.; Engelmann, B.; Massberg, S.
Summary: Deep vein thrombosis (DVT) is a common condition characterized by the formation of an occlusive blood clot in the venous vascular system, potentially complicated by detachment and embolization of thrombi into the lung. Recent evidence from mouse models has shed light on the sequence of events and on the cellular (innate immune cells, platelets) and molecular (hematopoietic tissue factor, nucleic acids) components involved. In response to decreased blood flow, circulating neutrophils and monocytes adhere to the activated endothelium within hours. They initiate and propagate DVT by interacting with platelets and by the exposure and activation of circulating tissue factor and FXII. Intravascular blood coagulation is also induced by extracellular nucleosomes released mainly from activated neutrophils. Interestingly, these mechanisms are closely linked to an evolutionary conserved immune defense mechanism activated in response to infections. In this review, we will give an overview of DVT and the role of innate immune pathways supporting this process. While the latter are aimed at preserving tissue integrity and function, uncontrolled blood coagulation and activation of immune cells may result in pathological thrombus formation and vascular occlusion. Understanding the molecular and cellular players triggering occlusion of large veins, and their distinction from physiological hemostasis, is important for the development of strategies to prevent and treat DVT.